2008
DOI: 10.1387/ijdb.072514jd
|View full text |Cite
|
Sign up to set email alerts
|

Expression and comparative genomics of two serum response factor genes in zebrafish

Abstract: Serum response factor (SRF) is a single copy, highly conserved transcription factor that governs the expression of hundreds of genes involved with actin cytoskeletal organization, cellular growth and signaling, neuronal circuitry and muscle differentiation. Zebrafish have emerged as a facile and inexpensive vertebrate model to delineate gene expression, regulation, and function, and yet the study of SRF in this animal has been virtually unexplored. Here, we report the existence of two srf genes in zebrafish, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We found that many cardiac muscle-specific SRF/MRTF-A target genes, such as cardiac alpha actin , smooth muscle alpha actin , cardiac actin smooth muscle , skeletal alpha actin , smooth muscle 22a , srf , and calponin (Chong et al, 2012; Davis et al, 2008; Descot et al, 2009) were markedly reduced in mical2b knockdown animals (Figure 5H). The control genes vascular endothelial growth factor ( vegf ), fibroblast growth factor 4 ( fgf4 ), and ETS translocation variant 4 ( pea3) which regulate MRTF-A-independent cardiac development in zebrafish, were not affected by mical2b knockdown (Figure 5H) (Liang et al, 2001; Znosko et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…We found that many cardiac muscle-specific SRF/MRTF-A target genes, such as cardiac alpha actin , smooth muscle alpha actin , cardiac actin smooth muscle , skeletal alpha actin , smooth muscle 22a , srf , and calponin (Chong et al, 2012; Davis et al, 2008; Descot et al, 2009) were markedly reduced in mical2b knockdown animals (Figure 5H). The control genes vascular endothelial growth factor ( vegf ), fibroblast growth factor 4 ( fgf4 ), and ETS translocation variant 4 ( pea3) which regulate MRTF-A-independent cardiac development in zebrafish, were not affected by mical2b knockdown (Figure 5H) (Liang et al, 2001; Znosko et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…These markers include mainly contractile, cytoskeletal and cytoskeleton-associated proteins such as smooth muscle alpha-actin, Sm22alpha, smooth muscle myosin heavy chain, and Smoothelin. Similarly, in zebrafish, the heterogeneity of MCs precludes their identification by single markers (Georgijevic et al, 2007; Davis et al, 2008). Therefore, we identified and cloned a panel of zebrafish MC markers including the genes encoding Transgelin (Sm22alpha-b), Transgelin2 (Sm22alpha-a), Acta2, Myh11, Smoothelin, Calponin, and Desmin.…”
Section: Resultsmentioning
confidence: 99%
“…S RF, a conserved transcription factor during evolution and encoded by a single gene with the exception of zebrafish, 1 is at the confluence of multiple signalling pathways controlling the transcription of immediate-early response genes and muscle-specific genes. 2 It is a member of the MADS box family of transcription factors, and binds the core sequence of CArG boxes [CC (A/T) 6 GG] as a homodimer 2 .…”
Section: General Featuresmentioning
confidence: 99%